Mapping and validation of a novel major QTL for resistance to stripe rust in four wheat populations derived from landrace Qishanmai - Jiang, Xu; Wang, Zhen; Feng, Jing; Du, Ziyi; Zhang, Zhongjun; Zhang, Yibin; Che, Mingzhe; Ren, Junda; Wang, Haiguang; Quan, Wei (Frontiers in Plant Science, 2023)
Wheat yield has been constrained by stripe rust disease globally. A wheat landrace (Qishanmai, QSM) consistently showed lower stripe rust severities in multiple year studies than susceptible check varieties including Suwon11 (SW) at the adult plant stage. To detect QTL for reducing the severity in QSM, 1218 recombinant inbred lines (RILs) were developed from SW × QSM. QTL detection was conducted firstly using 112 RILs selected for similarity in pheno-morphological characters. The 112 RILs were assessed for stripe rust severity at the 2nd leaf, 6th leaf and flag leaf stages under field and greenhouse conditions, and were genotyped using a 90 K single nucleotide polymorphism (SNP) wheat array. On the basis of these phenotypic and genotypic data, a major QTL (QYr.cau-1DL) was detected on chromosome 1D at the 6th leaf and flag leaf stages. Then, using 1218 RILs and new simple sequence repeat (SSR) markers developed according to the reference sequence IWGSC RefSeq v1.0, location of QYr.cau-1DL was refined to a 0.5 cM (5.2 Mb) interval flanked by SSR markers 1D-320.58 and 1D-325.79. Selection for QYr.cau-1DL was conducted by using these two markers to screen three F2 or BC4F2 populations (RL6058 × QSM, Lantian10 × QSM and Yannong21 × QSM). F2:3 or BC4F2:3 families derived from the selected plants were assessed for stripe rust resistance in the fields of two locations and in a greenhouse. Wheat plants carrying the resistant marker haplotype in homozygous state for QYr.cau-1DL showed lower stripe rust severities (by 44% to 48%) than plants lacking this QTL. The trial of RL6058 (a carrier of Yr18) × QSM also indicated that QYr.cau-1DL had larger effect than Yr18 on reducing severity; they acted synergistically, yielding an elevated level of stripe rust resistance.